Prerequisites for biocrops Up-Scaling I: An assessment of seed propagation of oilferous plant species with potential for biodiesel production - Nyomora, Agnes MS; Masomhe, Esther P (Tanzania Journal of Science, 2021)
This study assessed the propagation of non- edible oil plant species with potential for biodiesel production on 4 potting media forest, sandy, clay and loamy soil using seeds. Investigation was based on assessment of seed germination capacity, rooting ability and seedling growth rate of six selected plant species Telfairia pedata, Jatropha curcas, Excoecaria bussei, Croton macrostachyus, Croton megalocarpus and Ricinus communis. Completely randomized design (CRD) was adopted for this study using 10 seeds per plot (5L capacity pots) with 4 replications. An ANOVA was conducted to test for the significance of the treatments while Tukey-Kramer Multiple Comparisons test was used to test for the differences between treatment means. Species giving highest germination percentage also portrayed highest germination energy. Telfairia pedata grew luxuriously in all soil types while Jatropha curcas performed poorly in almost all soil types except in loam soil. Ricinus communis and Excoecaria bussei growth were moderate. Based on propagation ability and growth performance; multiplication by seeds was recommended for Telfairia pedata, Ricinus communis, Excoecaria bussei and Telfairia pedata but not for Croton macrostachyus, Croton megalocarpus which did not germinate at all. Croton seems to be recalcitrant and probably needed special attention and shortest storage time from harvesting prior to sowing